The Role of Internal Audit in Maintaining Financial Accountability and Transparency in Government Agencies: Literature Review - Middin, Muslianti; Nirwana, Nirwana; Haliah, Haliah (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to examine the role of internal audit in maintaining financial accountability and transparency in government agencies. Internal audit plays a crucial role in ensuring good governance, transparency in financial management, and fraud prevention. The study identifies key factors that support the role of internal audit, such as strengthening internal control systems, improving auditor competence, and implementing effective audits. Additionally, internal audit provides strategic recommendations to enhance accountability in the public sector. With strict oversight and a robust audit system, government agencies can prevent fraud and maximize budget efficiency. In conclusion, internal audit functions as both a supervisory tool and a strategy to strengthen financial governance and increase public trust.